Research note: Effect of diet based corn fodder on semen quality of Ettawah grade bucks - Nuswantara, Limbang Kustiawan; Setiatin, Enny Tantini; Pujaningsih, Retno Iswarin; Samsudewa, Daud; Ondho, Yon Soepri; Sutiyono, Sutiyono; Tampubolon, Baginda Iskandar Muda; Prahara, Pupus Galau; Mustofa, Fatmawati; Setiaji, Asep (Journal of Advanced Veterinary Research, 2025)
This study evaluated the impact of corn fodder supplementation on the semen quality of Ettawah grade bucks. The bucks used in this study were three Etawah crossbred goats with ages 2-6 years. Feed treatment this study, T0: Concentrate without corn fodder, T1: Concentrate with corn fodder. The parameters observed were: Macroscopic parameters included volume, colour, consistency, and pH; and microscopic parameters included mass motility, motility, viability, abnormality, concentration. Results revealed that the addition of corn feed to the diet of bucks did not have a significant effect on sperm quality macroscopically, but it did improve microscopic indicators such as motility and viability. However, there was an increase in abnormalities and a decrease in sperm concentration, which raises concerns about the overall reproductive potential of bucks. Therefore, further research is needed to determine the optimal corn feed mixture in the diet and to investigate mitigation strategies for the negative effects on sperm quality.